Prompting Learning Method Approach in Inclusive Education for Autistic Children - Putri Sari Ulfa Sembiring; Dewi Sartika Panggabean (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2025)
The purpose of this study is to find out theoretically that in psychology books and articles on children with special needs found in journals Early childhood education has various research results that explain various methods that can be applied to children with special needs. The results of this research can be used as reading material, references and as guidelines for teachers and especially parents in practicing providing services to their children. The method in this study in qualitative form using a literature review (Library research). The researcher conducted a literature review of books and scientific works that discuss autistic children and their services. Data sources The articles used are relevant articles and books related to the discussion. The sources used are 31 with details of 20 articles specifically discussing autistic children, 8 articles discussing inclusive education and the prompting methods provided while 3 other articles discussing the definition of early childhood education. The data analysis techniques used in this study are data collection, data reduction, data presentation, and conclusions. The results of this study are expected to be new findings and references in the world of education, especially inclusive education, that the prompts method can be used as an alternative therapy for autistic children.